Efficacy and safety of chimeric antigen receptor T-cell (CAR-T) therapy in patients with haematological and solid malignancies: protocol for a systematic review and meta-analysis. Issue 12 (29th December 2017) - Grigor, Emma J M; Fergusson, Dean A; Haggar, Fatima; Kekre, Natasha; Atkins, Harold; Shorr, Risa; Holt, Robert A; Hutton, Brian; Ramsay, Tim; Seftel, Matthew; Jonker, Derek; Daugaard, Mads; et al.
Abstract : Introduction: Patients with relapsed or refractory malignancies have a poor prognosis. Immunotherapy with chimeric antigen receptor T (CAR-T) cells redirects a patient's immune cells against the tumour antigen. CAR-T cell therapy has demonstrated promise in treating patients with several haematological malignancies, including acute B-cell lymphoblastic leukaemia and B-cell lymphomas. CAR-T cell therapy for patients with other solid tumours is also being tested. Safety is an important consideration in CAR-T cell therapy given the potential for serious adverse events, including death. Previous reviews on CAR-T cell therapy have been limited in scope and methodology. Herein, we present a protocol for a systematic review to identify CAR-T cell interventional studies and examine the safety and efficacy of this therapy in patients with haematology malignancies and solid tumours. Methods and analysis: We will search MEDLINE, including In-Process and Epub Ahead of Print, EMBASE and the Cochrane Central Register of Controlled Trials from 1946 to 22 February 2017. Studies will be screened by title, abstract and full text independently and in duplicate. Studies that report administering CAR-T cells of any chimeric antigen receptor construct targeting antigens in patients with haematological malignancies and solid tumours will be eligible for inclusion. Outcomes to be extracted will include complete response rate (primary outcome), overall response rate, overall survival, relapse and adverse events. A meta-analysis will be performed to synthesise the prevalence of outcomes reported as proportions with 95% CIs. The potential for bias within included studies will be assessed using a modified Institute of Health Economics tool. Heterogeneity of effect sizes will be determined using the Cochrane I 2 statistic. Ethics and dissemination: The review findings will be submitted for peer-reviewed journal publication and presented at relevant conferences and scientific meetings to promote knowledge transfer. PROSPERO registration number: CRD42017075331 .